Is Hyde Park Hiding the Truth? An Analysis of the Public Interest Defence to Copyright Infringement - Yurkowski, Rachel A (Victoria University of Wellington Law Review, 2001)
The existence, or not, of a public interest defence in the sphere of copyright law has been an issue of contention for many years. Due to the comprehensive statutory fair dealing defences available, only a handful of defendants have sought to rely on this defence, which exists at common law. However, when the defence has been raised, the judges have been unable to reach a consensus on its status, scope and indeed availability as a defence to breach of copyright. This paper analyses the extent to which public interest concerns are addressed in statutory copyright law, and presents arguments in support of extending the common law public interest defence to copyright law. However, any such defence must be limited in its scope and applicability, so as to avoid becoming a "thieves charter".